2nd International Multidisciplinary Microscopy and Microanalysis Congress Proceedings of InterM, October 16-19, 2014 - Polychroniadis, E.K.; Oral, Ahmet Yavuz; Ozer, Mehmet; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The 2nd International Multidisciplinary Microscopy and Microanalysis Congress & Exhibition (InterM 2014) was held on 16–19 October 2014 in Oludeniz, Fethiye/ Mugla, Turkey. The aim of the congress was to gather scientists from various branches and discuss the latest improvements in the field of microscopy. The focus of the congress has been widened in an "interdisciplinary" manner, so as to allow all scientists working on several related subjects to participate and present their work. These proceedings include 33 peer-reviewed technical papers, submitted by leading academic and research institutions from over 17 countries and representing some of the most cutting-edge research available. The papers were presented at the congress in the following sessions: ·         Applications of Microscopy in the Physical Sciences ·         Applications of Microscopy in the Biological Sciences.
Part 1: Applications of Microscopy in the Physical SciencesElectron Microscopy study of Thermoelectric (BixSb1-x)2Te3 thin film .-Structural characterization of layers for advanced non-volatile memories -- Advanced technology for Analytical Electron Microscopy by using Aberration corrected Transmission Electron -- TEM characterization of a complex twinning system in 3C- SiC -- Microstructural Evaluation of Suspension Thermally Sprayed WC-Co Nanocomposite Coatings -- Wavelength depended speckle correlation analyses of engineered metal surfaces -- Effect Of V2O5  Additives  To The  Sintering Of Y2O3 -- Integrating microscopic analysis into existing quality assurance processes -- Effect of annealing temperature on the structural and Magnetic Properties of Terbium Iron Garnet Thin Films Prepared by Sol-Gel Method -- Fibrous growth of chloride minerals on diatomite saturated with a brine -- Fractal characteristics of the pore network in diatomites using mercury porosimetry and image analysis -- Development of an off-axis digital holographic microscope for large scale measurement in fluid mechanics -- SEM-EDS observation of structure changes in synthetic zeolites modified for CO2 capture needs -- SEM investigation of microstructures in hydration products of portland cement -- Some Properties of 1.3343 Steel Treated by Pulse Plasma Technique -- Investigation of Microstructure of Ceramics Produced from Gabbro and Zeolite Raw Materials -- The effect of MgO and MgO-Al2O3 on zirconia produced by precipitation method -- Microstructural Investigation of IF Steels Joined by Metal Inert Gas Brazing -- An ESEM/EDX methodology for the study of additive adsorption at the polymer-air interface -- Enhanced Confocal Fluorescence Microscope performance using a differential pinhole -- Thermal neutron detection by entrapping 6LiF nanodiamonds in siloxane scintillators -- High temperature reliability of Ta-based and TiW-based diffusion barriers -- The Direct Observation of Grain Refinement Mechanism in Advanced Multicomponent γ-TiAl Based Structural Intermetallics Doped with Boron -- Low Temperature Resistivity of the Rare Earth Diborides (Er, Ho, Tm)B2 -- Influence of mechanical parameters on the   friction and wear of sliding brass-steel Couple -- Measuring the degree of sensitization (DOS) using an electrochemical technique -- Substitution for Chromium and Nickel in Austenitic Stainless Steels -- Part 2: Applications of Microscopy in the Biological Sciences -- Ca, P and collagen fibrils period measurements in the vertebras of  lordotic Sparus aurata -- Use of Bone marrow-derived Mesenchymal Stem Cells in Improving Thioacetamide Induced Liver Fibrosis in Rats -- Electrochemical Detection of Nicotine using Cerium Nanoparticles Modified Carbon Paste Sensor and Anionic Surfactant -- Exploring the Antibiotic Effects in Bacterial Biofilms by Epifluorescence and Scanning Electron Microscopy -- Quantitative confocal microscopy analysis as a basis for search and study of potassium Kv1.x channel blockers -- Analysis of nucleosome transcription using single-particle FRET.
Keywords: Spectroscopy; Microscopy; Materials science; Biophysics; Biological physics; Spectroscopy and Microscopy; Spectroscopy/Spectrometry.; Biological Microscopy; Characterization and Evaluation of Materials; Biological and Medical Physics, Biophysics